Association between rs571312 MC4R and rs3810291 TMEM160 single-nucleotide polymorphisms and metabolic surgery outcomes - Kobzar, P. A. (General Surgery, 2025)
Objective – to determine the association between the SNP rs571312 MC4R and SNP rs3810291 TMEM160 genes and the results of metabolic surgery. Materials and methods. A prospective, observational, monocentric cohort study was conducted at the Department of General Surgery No2 of Bogomolets National Medical University. A total of 112 patients with surgical indications were offered bariatric surgery. Patients who agreed to undergo bariatric surgery (n=53) comprised the main group. Those who refused surgical treatment (n=59) formed the control group. The main group underwent bariatric interventions, including laparoscopic gastric bypass and laparoscopic sleeve gastrectomy, whereas patients with BMI ≥50 kg/m2 had a twostage surgical treatment involving intragastric balloon placement for a period of 6 months, followed by gastric bypass within 14 days after balloon removal. The results for both groups were evaluated one year after the start of treatment. In the control group, 59 patients suffering from obesity received conservative treatment. Before the start of treatment, all patients underwent anthropometric examinations and analysis of buccal epithelial scrapings. Genetic studies included DNA collection and isolation, as well as genotyping to determine polymorphisms of the rs571312 MC4R and rs3810291 TMEM160 genes. Results. A strong correlation was found between bariatric surgery outcomes and the presence of rs571312 MC4R and rs3810291 TMEM160 gene polymorphisms in the study group (r=0.622; p≥0.001). There was no significant association between the degree of gene dominance and bariatric surgery outcomes (r=0.112, p≥0.5). Conclusions. In the studied cohort, a relationship was found between the effectiveness of bariatric procedures and the presence of the rs571312 MC4R (r=0.465) and rs3810291 TMEM160 (r=0.55) polymorphisms, as well as the concurrent presence of both polymorphisms (r=0.622). The detection of these polymorphisms is associated with bariatric surgery outcomes, regardless of the degree of their genetic dominance (r=0.467).